Consumer Satisfaction among the Young Youth Using Smart Phones: A Study - Jain, Stuti; Sarangdevot, Shiv Singh (International Journal of Computer Sciences and Engineering, 2019)
The smart phone industry is the fastest growing sector in India. During this 25 years of journey mobile phones were transformed into personal computers. It is growing at a very rapid pace and has a significant contribution to the Gross Domestic Product of India every year. There is a great evolution of varied smart phones by different brands depending upon customer awareness and customer satisfaction. The new smart phones are featured with artificial intelligence, HD display, virtual assistant features like SIRI, Google assistant etc., high powered cameras, HD quality photos, Cloud storage feature and better battery life. As per study conducted by the mobile ecosystem forum, highest penetration rate of smart phone users was in the age group of 16-35 years of old. The study of customer satisfaction is relevant for organizations to maintain long term and healthy relationship with customers. In the carried out study, a survey was presented to understand the significant relationship between smart phone features and Indian youth customer. Presented paper also presents the comparative analysis which gives an overview of key findings by various researches along with their concept used for analysis.